Estudo da flexão em vigas de concreto leve armado - Levi, Alejandro Carlos Adolfo Arce (1974)
The subject of this dissertation deals with the bending analysis of light. Our final aim is to compare the experimental results with the CEB-FIP standards for this type of concrete. Twelve specimens were tested. All the beams tested were casted with the same geometry and dimensions, only the geometrical percentage of the reinforcement was a varied for each pair of beams. The experimental results are compared with those obtained by theoretical analysis taking into account the CEB-FIP recommendations.